Roommate matching system by applying a pyramick model / Aqil Izzuddin Shamsul Arifin - Shamsul Arifin, Aqil Izzuddin (2017)
College Administrative that are located in the University Teknologi Mara Kampus Jasin are having a problem when the new student wants to register in the college. The college administrative does not have any computerized system that could help to overcome this problem. The company also does not keep any student information in the computerized system. Besides, all universities around Malaysia have been using random matching system in order to match roommate for new students in every semester. This project is named as e-Roommatch. The requirements for this project were collected by questionnaire and interview of the stakeholder and the student itself. Students will be registered to their room in order from the first empty room till the last one. Through the research that had been done in developing a Roommates Matching System using the concept of metaphysics science, which is known as PYRAMICK Technique which uses the date of birth value as the parameter is a systematic way to know the background of students so that we can find the matching partner or roommate for them. This is to reduce the conflicts among roommates which may affect their studies. It is hoped this system would help students have a better roommate and will help in their studies. For the future work it is suggested that this system combines other techniques using psychological methods such as "Rahsia Bulan Kelahiran" and “Personaliti Warna”. By using more than one technique, this system is expected to provide better result in order to match student’s roommate.